The Public Communication Model of the Government of Gorontalo Province as a Strategy for Enhancing Public Trust from a Governance Perspective - Supriyanto M. Radjak; Arifin Tahir; Sukarman Kamuli (Ilomata International Journal of Social Science, 2026)
This study examines how the Government of Gorontalo Province operationalizes public communication as a governance strategy to strengthen public trust. While prior studies discuss public communication and good governance normatively, this research contributes by empirically mapping how transparency, participation, responsiveness, and accountability are practiced and interconnected within a provincial government setting. Using a qualitative case study design, data are collected through in-depth interviews with purposively selected informants, non-participant observations, and document analysis. Thematic analysis is applied to identify communication patterns and governance dimensions. The findings show that public communication is predominantly informational, with limited but emerging dialogical elements. Informants perceive that transparency and responsiveness are relatively evident in service delivery, whereas participation and accountability remain largely procedural. Within this case context, these patterns shape public perceptions of openness and fairness, indicating that strengthening dialogical and participatory communication is essential for sustaining public trust in local governance.